A Model of Ideological Thinking - Yves Le Yaouanq (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper develops a theory in which heterogeneity in political preferences produces a partisan disagreement about objective facts. A political decision involving both idiosyncratic preferences and scientific knowledge is considered. Voters form motivated beliefs in order to improve their subjective anticipation of the future political outcome. In equilibrium, they tend to deny the scientific arguments advocating the political orientations that run counter to their interests. Collective denial is the strongest in societies where contingent policy is the least likely to be implemented, either because of votersíntrinsic preferences or because of rigidities in the political process. The theory predicts that providing mixed evidence produces a temporary polarization of beliefs, but that disclosing unequivocal information eliminates the disagreement.
Keywords: D72; D81; D83; D84; Z13; 330; beliefs; ideology; cognition; disagreement; polarization